Delaminated Fracturing and its Controls on Hydrocarbon Accumulation in Carbonate Reservoirs of Weak Deformation Regions: A Case Study of the Yuanba Ultra-Deep Gas Field in Sichuan Basin, China - Wang, Xinpeng; Chen, Shuping; Feng, Guimin; Xiao, Zhuang; Yuan, Haowei; Xu, Shidong; Zhao, Huaibo (Frontiers in Earth Science, 2022)
Since discovering Yuanba gas reservoir, there has been no unified conclusion of hydrocarbon accumulation. The Feixianguan Formation micrite and argillaceous limestone are controversial as the direct cap rock. This research analyzed the integrity of the limestone layer from delaminated fracturing to judge whether it can be as the cap rock and then discuss the mechanism of accumulation. Delaminated fracturing and its controls on hydrocarbon accumulation were studied using seismic data, well logging data, rock mechanic measurements and petroleum geological data. Mudstones from the Upper Permian Wujiaping Formation serve as the source rock. Changxing Formation dolomite from the upper Permian is the reservoir rock. The caprock is marlites from the Lower Triassic Feixianguan Formation. The Changxing Formation had middle-high dip angle fractures formed by integrating pore fluid pressures and the tectonic stresses in the Late Triassic Indosinian Movements. The Feixianguan Formation had horizontal stylolites and fewer fractures, which kept the Feixianguan Formation marlites good cap rocks. The adjacent Feixianguan and Changxing formations have their fracture system known as delaminated fractures.As a result, the upper Permian Changxing Formation dolomite has good reservoir properties, while the Lower Triassic Feixianguan Formation limestone or marlites have good capping performance. These delaminated fractures are formed because of different lithologies and thicknesses in the carbonate rock series. It is the key factor in controlling the formation of Yuanba Gas Filed with weak deformation. Delaminated fracturing suggests a significant exploration potential in carbonate strata with weak deformation, particularly in ultra-deep areas.